Police transformation within constitutional democracy design: Evidence from Indonesia - Ismail Hasani; Halili; Ikhsan Yosarie (Jurnal Civics: Media Kajian Kewarganegaraan, 2026)
Indonesian National Police (Polri) institutional position following the 1998 political transition remains a contested terrain, particularly in reconciling operational independence with the demands of democratic governance. This study investigates how Polri has navigated that tension, drawing on a mixed-methods design that integrates diagnostic mapping of 130 institutional problems, structured surveys with 167 experts distributed across 50 districts and cities, and a comparative analysis of policing frameworks in France and the Netherlands. The findings expose a fundamental contradiction within Act No. 2/2002. While the legislation formally separates Polri from military structures, it simultaneously creates an accountability vacuum, a concern reflected in the 61.7% of expert assessments that are unfavourable. Field data further document three entrenched dysfunctions: a militaristic organisational culture, integrity failures concentrated in investigative units, and chronic service deficiencies flagged repeatedly in ombudsman evaluations between 2020 and 2023. Building on these findings, the study advances a transformation framework organised around four mutually reinforcing pillars: humanist policing grounded in rights protection, anti-corruption governance through merit-based systems, technology-enabled service modernisation, and community-centred precision policing. Proposed reforms target legislative revision, restructuring of professional education, and the development of civilian oversight mechanisms with genuine supervisory authority. The study offers a replicable analytical model for evaluating police reform trajectories in post-authoritarian democratic settings.